Some Remarks on Memory and Heritage in Europe - Zdzisław Mach (Ksiegarnia Akademicka Publishing, 2018)
The text concludes the contributions of the volume, accentuating the general reflections on European heritage which can be found described herein by the articles’ authors. The conclusion refers to the general ideas of Europe with its specific values and the concepts of democratization, dealing with collective trauma as well as various narrative strategies used in the process of heritage invention and social use. Finally, a significant example of heritage interpretation is provided and focused on in the form of the #heritage exhibition held at the National Museum in Kraków. Special attention in this case is drawn to two contradictory paradigms of heritage interpretation, while the exhibition becomes a symbol of the complexity of the present debate on European identity in contemporary Poland/Europe.